Targeted Interventions for the Preservation of Traditional Himalayan Buddhist Culture: An Evaluative Case Study of Ananda Sangh, Kathmandu, Nepal - KC, Dipendra Bahadur (Rural Development Journal, 2026)
This paper analyses the selected intervention initiatives that the Ananda Sangh has undertaken to conserve the traditional Himalayan Buddhist culture as well as to meet the educational and social demands of the marginalized groups of people in Budhanilkantha-11, Kathmandu, Nepal. A case study design based on mixed methods was used to collect primary data in the form of key informant interviews (n = 12), focus group discussions (n = 3), and structured surveys of monk students between September and November 2023. The 46 monks (20% of 230 beneficiaries overall) were chosen as the stratified random sample of participants in the survey component. The secondary data included project reports, evaluation documents of the Social Welfare Council and other literature. It has been found that the interventions of Ananda Sangh were effective to offer quality education to 230 monks representing the most remote marginalized communities, as well as residential facilities, nutrition, and healthcare services. The program has proven to have positive effects in three main areas namely education, health and preservation of the culture. The evaluation of the program demonstrated that it is in line with constitutional goals, efficiency in program operations, and effectiveness in producing short-term educational results. Nevertheless, there are still crucial weaknesses in the alignment of policy and practice, especially as it pertains to social auditing procedures and adherence to gender equity. This research is relevant to the realization of ways in which faith-based organizations can be able to combine the hope of cultural preservation and goal of social welfare within the Nepal constitutional framework of secularism and religious freedom